Application of polymerase chain reaction for early detection of infectious bursal disease virus infection - PARTHIBAN, M; THIAGARAJAN, V (The Indian Journal of Animal Sciences, 2014)
The bursae suspensions at different hours post- infection were subjected to AGPT, dot-ELISA and RT-PCR to compare their sensitivity in detecting the presence of IBD virus in the early stage of infection. Until 36 hr post - Infection, the antigen could not be detected by AGPT and dot-ELISA, whereas it was pOSSible to detect Viral RNA by RT-PCR at 14 hr post - infection. Hence, RT-PCR was highly sensitive in detecting the Virus dunng early stage of IBDV infection.